1981
DOI: 10.1017/s0001867800036508
|View full text |Cite
|
Sign up to set email alerts
|

Risk-sensitive linear/quadratic/gaussian control

Abstract: The conventional linear/quadratic/Gaussian assumptions are modified in that minimisation of the expectation of cost G defined by (2) is replaced by minimisation of the criterion function (5). The scalar –θ is a measure of risk-aversion. It is shown that modified versions of certainty equivalence and the separation theorem still hold, that optimal control is still linear Markov, and state estimate generated by a version of the Kalman filter. There are also various new features, remarked upon in Sections 5 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
227
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(228 citation statements)
references
References 2 publications
1
227
0
Order By: Relevance
“…Because some of the timing protocols correspond to nonsequential or 'static' games while others enable sequential choices, equivalence of equilibrium outcomes implies a form of dynamic consistency. Jacobson (1973) and Whittle (1981) first showed that the risk-sensitive control law can be computed by solving a robust penalty problem of the type we have studied here, but without discounting. Subsequent research reconfirmed this link in nonsequential and undiscounted problems, typically posed in nonstochastic environments.…”
Section: Fear Of Model Misspecificationmentioning
confidence: 99%
“…Because some of the timing protocols correspond to nonsequential or 'static' games while others enable sequential choices, equivalence of equilibrium outcomes implies a form of dynamic consistency. Jacobson (1973) and Whittle (1981) first showed that the risk-sensitive control law can be computed by solving a robust penalty problem of the type we have studied here, but without discounting. Subsequent research reconfirmed this link in nonsequential and undiscounted problems, typically posed in nonstochastic environments.…”
Section: Fear Of Model Misspecificationmentioning
confidence: 99%
“…This results in a finite dimensional information state filter, but the static information state feedback control law is calculated off line by (singly not doubly) infinite dimensional dynamic programming equations. Of course, if the plant is additionally linear in the controis, and the index kernel is additionally quadratic in the controls, then this theory leads to known linear quadratic (risk sensitive) controllers [8,20]. These controllers are of course linear and have the same dimension as the plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is only in [2] that the complete solution to this problem was finally obtained. The discrete-time partial observation problem was solved by Whittle in [18] (see also [19]). An important relation with robust controllers was found in [5], [6], whereas the risk-sensitive maximum principle was studied in [14], [15], [8], [10].…”
Section: [X (T)qx(t) + U (T)ru(t)]dt (2)mentioning
confidence: 99%
“…Assumption 5 There exist unique global solutions P (·) and U (·) to equations (18) and (19), respectively.…”
Section: Assumptionmentioning
confidence: 99%